Strategic Capabilities and SME Internationalization: The Effects of Innovation and Digitalization among Indonesian SMEs - Muhammad Tody Arsyianto; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Small and medium-sized enterprises (SMEs) play a central role in the Indonesian economy, yet their internationalization remains limited. This condition indicates that many SMEs have not fully transformed innovation and digitalization into strategic capabilities that support broader market expansion. This study examines the effects of innovation and digitalization on SME internationalization from the strategic capability perspective. A quantitative explanatory design with a cross-sectional survey was employed. The sample consisted of 200 SME owners or main managers in East Java selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The simulated results indicate that innovation and digitalization positively contribute to SME internationalization through product value enhancement, business process efficiency, and broader market reach. These findings suggest that SME internationalization is more likely to emerge when innovation and digitalization are integrated as strategic capabilities rather than treated as isolated initiatives.